2022
DOI: 10.1177/10760296221078837
|View full text |Cite
|
Sign up to set email alerts
|

Low Mean Platelet Volume is Associated with Deep Vein Thrombosis in Older Patients with Hip Fracture

Abstract: This study aimed to explore the association between mean platelet volume (MPV) and preoperative deep vein thrombosis (DVT) in older patients with hip fracture. A total of 352 consecutive older patients with hip fracture were included from January 2014 to December 2020. MPV values were measured on admission, and color Doppler ultrasonography was performed for DVT screening before the planned surgery. The receiver operating characteristic (ROC) curve was used to establish the optimal cut-off value for the predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
(67 reference statements)
1
6
0
Order By: Relevance
“…Of note, the significant difference in pre-chemotherapy fibrinogen levels should be interpreted with caution due to the low number of patients, low event rate and the inclusion of female-only studies. Nonetheless, the findings of increased VTE risk in patients with elevated or decreased biomarker levels we report in this paper are aligned with other studies evaluating the same biomarkers levels at the time of VTE in cancer patients, [145][146][147][148] as predictors of first symptomatic provoked VTE, 149,150 and as risk factors in the general population. [151][152][153] This supports that certain biomarkers could play a role in the prediction of VTE.…”
Section: Introductionsupporting
confidence: 90%
“…Of note, the significant difference in pre-chemotherapy fibrinogen levels should be interpreted with caution due to the low number of patients, low event rate and the inclusion of female-only studies. Nonetheless, the findings of increased VTE risk in patients with elevated or decreased biomarker levels we report in this paper are aligned with other studies evaluating the same biomarkers levels at the time of VTE in cancer patients, [145][146][147][148] as predictors of first symptomatic provoked VTE, 149,150 and as risk factors in the general population. [151][152][153] This supports that certain biomarkers could play a role in the prediction of VTE.…”
Section: Introductionsupporting
confidence: 90%
“…A research in China reported that the incidence was 15.1% and found that low MPV was associated with DVT in Older Patients with Hip Fracture. 9 Ferroni et al 19 demonstrated that low level of MPVs in cancer patients before chemotherapy was a predictor of increased risk venous thromboembolism risk while the similar result was confirmed in another researche in cancer patients from Australia. 20 In the emergency department, a retrospective study conducted in Italy supported an inverse association between MPV and the risk of DVT.…”
Section: Discussionmentioning
confidence: 74%
“…The cut-off point according to the ROC curve for MPV was 13.3 fL, and multivariate logistic regression analysis showed that MPV level below 13.3 fL was significantly associated with an increased risk of DVT (OR = 4.857), and with every 1.0 fL decrease in MPV, the risk increased by 27.7%. 9 Although the subject of their study, like the present one, were older patients, it focused on those with hip fracture and it had a small sample size (352 cases), and only investigated the association between MPV and DVT. Ma J et al reported that the risk of preoperative DVT increased by 3.06 times in PDW<12% patients with foot fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Braekkan et al found that increased MPV is associated with increased risk of VTE, 8 while Wang Z et al found that low MPV levels are associated with DVT in older patients with hip fracture. 9 Ma J et al reported that PDW (<12%) is a risk factor for preoperative DVT in patients with foot fracture. 10 Grotto HZ et al found that P-LCR may be used as an indicator of risk factor for thromboembolic ischemic events.…”
Section: Introductionmentioning
confidence: 99%